Culinary traditions beyond ingredients: Identifying ceramic vessels used in cooking practices of the South Central Andes - Scaro, Agustina (2021)
Culinary knowledge, traditional dishes, preparation forms and equipment, and commensality practices, within Andean cosmovision, involve a way of understanding the world. They are transmitted from generation to generation, thus constituting the culinary heritage. The study of culinary knowledge and practices, its loss or adaptation provide information about the social, economic and productive life of the communities. Even more, it addresses changes and continuities in communities? lifestyle, as reflected in their food. In the last fifteen years, Quebrada de Humahuaca (North of Argentina) has been the scenario where culinary heritage was rediscovered. Recipes and ingredients found in different Andean environments were highlighted and revalued from traditional to tourist and ?haute cuisine? contexts. However, old-style equipment, especially ceramic pots and wooden utensils, have been replaced almost entirely by metal and plastic ones. This paper aims to infer about possible uses given to archaeological ceramic vessels in traditional Andean culinary preparations. We did the survey based on published local cookbooks, ethnographic records of roasted corn/beans and chicha. Morpho-functional and use-alteration study of archaeological vessels were also carried out. The latter were recovered in the south-central sector of Quebrada de Humahuaca. From this multidisciplinary approach, we seek to advance in the understanding of past culinary practices and the role that vessels played in various contexts of food preparation and commensality. Likewise, to revalue traditional knowledge and practices related to the South-Central Andes Culinary Heritage.